2005
DOI: 10.1090/conm/379/07025
|View full text |Cite
|
Sign up to set email alerts
|

A tail-matching method for the linear stability of multi-vector-soliton bound states

Abstract: Linear stability of multi-vector-soliton bound states in the coupled nonlinear Schrodinger equations is analyzed using a new tailmatching method. Under the condition that individual vector solitons in the bound states are wave-and-daughter-waves and widely separated, small eigenvalues of these bound states that bifurcate from the zero eigenvalue of single vector solitons are calculated explicitly. It is found that unstable eigenvalues from phase-mode bifurcations always exist, thus the bound states are always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Yang [33] studied analytically the linear stability of twovector solitons bound states in the coupled nls equations by a tail-matching method. He obtained some conditions for small eigenvalues and he showed that these bound states are always linearly unstable due to the existence of one unstable phase-induced eigenvalue.…”
Section: E55mentioning
confidence: 99%
See 4 more Smart Citations
“…Yang [33] studied analytically the linear stability of twovector solitons bound states in the coupled nls equations by a tail-matching method. He obtained some conditions for small eigenvalues and he showed that these bound states are always linearly unstable due to the existence of one unstable phase-induced eigenvalue.…”
Section: E55mentioning
confidence: 99%
“…Also, the stability properties of such solutions for external perturbations as well as during interactions among themselves have been studied both numerically [20,23] and analytically [33]. For example, numerical simulations of the propagation and interactions of one-dimensional Langmuir solitons and their generation from random fluctuations by an external pump field were presented by Ismail and Taha [20,21,22,23,24].…”
Section: E55mentioning
confidence: 99%
See 3 more Smart Citations